Da adulteração da ajuda ao desenvolvimento : a presença chinesa em África - Sousa, António Jorge Duarte Rebelo de, 1952- (2022)
Lusíada. Economia & Empresa. - ISSN 1645-6750. - N. 33 (2022). - p. 57-66.